Modern trends in teaching foreign languages and methods of expanding students' vocabulary - Urinova, Durdona Farhodovna (The Lingua Spectrum, 2026)
This scientific article comprehensively examines modern trends in foreign language teaching and innovative methods aimed at developing students’ vocabulary competence. The study analyzes the role of Communicative Language Teaching, Task-Based Learning, Project-Based Learning, gamification, multimedia technologies, digital platforms, and interactive teaching methods in contemporary foreign language education. Special attention is paid to the development of speaking skills, communicative competence, and lexical competence through modern pedagogical technologies. The article also discusses the effectiveness of digital platforms such as Quizlet, Kahoot, Duolingo, and Wordwall in vocabulary acquisition and language learning processes. The findings of the research demonstrate that communicative and technology-based methods significantly increase students’ motivation and interest in learning foreign languages, facilitate faster vocabulary retention, and improve learners’ ability to communicate fluently in English. Furthermore, the article highlights the pedagogical potential, practical significance, and educational advantages of innovative language teaching methods in modern educational systems. The study confirms that integrating interactive technologies and communicative methodologies into foreign language instruction contributes substantially to the effectiveness and quality of language education.